Penerapan Dasar dan Fungsi Manajemen Untuk Pengelolaan Pasar Rengrang dan Wisata di Desa Dawuhan Banjarnegara - Astohar Astohar; Dhian Andanarini Minar Savitri; Aditya Yoga Prasetya; Isna Azizah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The Dawuhan Tourism Village which consists of a swimming pool, river tubing, various games for children and adults as well as the Rengrang Market (Traditional Snack Market) is able to help the community maintain local culture and increase income. Pokdarwis, PKK and Karang Taruna as managers and members involved in the Tourism Village which consists of several units need to increase their capacity and capability through basic training and management functions. The service method uses lectures, discussions, simulations and questions and answers regarding the benefits and uses in preparing work programs and organizational structures. The results of the service show that different organizations in managing Tourism Villages and strategies for achieving their management require different methods of communication and delivery. It is necessary to apply andragogy learning so that presenters and participants can be more fluid and linear. Action is needed to provide confidence that the commitment conveyed is not just words, but real action and sincerity. It is necessary to increase the participation of Banjarnegara Regency Government officials (Cross Service) through community organizations in Dawuhan Village such as Pokdarwis, PKK, Karang Taruna which can be further increased with other organizations.